NILAI-NILAI PENDIDIKAN KARAKTER DALAM SURAT AL-KAHFI AYAT 66-82 PERSPEKTIF TAFSIR AL-MISHBAH - Khusna Aisi , Okta; Danik Prahastiwi , Eka; Dwi Cahyono , Dedi; Tias Aorta , Dian (As-Sulthan Journal of Education, 2024)
The Qur'an is the holy book revealed to Prophet Muhammad (peace be upon him) as a mercy and guidance for Muslims. Therefore, every behavior and character should align with the teachings of the Qur'an. Character education needs to be developed by instilling values derived from the stories in the Qur'an, which serve as exemplary lessons. In this context, this research aims to uncover the character values embedded in the story of Prophet Musa and Prophet Khidr in Surah Al-Kahf, verses 66–82, based on the interpretation of Tafsir Al-Mishbah by M. Quraish Shihab. This study is particularly significant given the increasing deviation of students’ behavior from the Qur'anic character values. Such conditions underscore the importance of teachers, parents, and education practitioners continuously enhancing their understanding of character education values, as exemplified in Surah Al-Kahf, verses 66–82.